Near-IR Electrochromic Film with High Optical Contrast and Stability Prepared by Oxidative Electropolymerization of Triphenylamine Modified Terpyridine Platinum(II) Chloride - Huiying Gu; Xiaomeng Sun; Qian Zhao; Hongwei Wang; Xinfeng Cheng; Chunxia Yang; Dongfang Qiu (Molecules, 2023)
Terpyridine (TPY) platinum(II) chloride with a triphenylamine (TPA) group was successfully synthesized. The strong intramolecular Donor(TPA)-Acceptor(TPY) interaction induced the low-energy absorption band, mixing the spin-allowed singlet dπ(Pt)→π*(TPY) metal-to-ligand charge transfer (MLCT) with the chloride ligand-to-metal charge transfer (LMCT) and chloride ligand-to-ligand (TPY) charge transfer (LLCT) transitions, to bathochromically shift to λmax = 449 nm with significant enhancement and broadening effects. Using the cyclic voltammetry method, its oxidative electropolymerization (EP) films on working Pt disk and ITO electrodes were produced with tunable thickness and diffusion controlled redox behavior, which were characterized by the SEM, EDS, FT-IR, and AC impedance methods. Upon applying +1.4 V voltage, the sandwich-type electrochromic device (ECD) with ca. 290 nm thickness of the EP film exhibits a distinct color transformation from red (CIE coordinates: L = 50.75, a = 18.58, b = 5.69) to dark blue (CIE coordinates: L = 45.65, a = −1.35, b = −12.49). Good electrochromic (EC) parameters, such as a large optical contrast (ΔT%) of 78%, quick coloration and bleaching response times of 2.9 s and 1.1 s, high coloration and bleaching efficiencies of 278.0 and 390.5 C−1·cm2, and good cycling stability (maintains 70% of the initial ΔT% value after 3200 voltage switching cycles), were obtained.